Identity fusion "in the wild": Moving toward or away from a general theory of identity fusion?. (27th December 2018) - Swann, William B.; Jetten, Jolanda
Abstract: Whitehouse's focus on two causes of identity fusion (evolution and shared experiences/biology) deepens understanding of these specific topics. While we applaud his analysis, in his efforts to elaborate these two causes, he has – perhaps unavoidably – produced a narrower conceptualization of identity fusion. This is unfortunate because it undermines his stated goal of developing a more general, encompassing theory.